Function and Compensatory Mechanisms Among the Components of the Chloroplastic Redox Network. (2nd January 2019) - Souza, Paulo V. L.; Lima-Melo, Yugo; Carvalho, Fabricio E.; Reichheld, Jean-Philippe; Fernie, Alisdair R.; Silveira, Joaquim A. G.; Daloso, Danilo M.
Abstract: Life on earth depends on the presence of photoautotrophic organisms that are able to input carbon into the ecosystems through the process of photosynthesis which, with a few specialized exceptions, takes place within the chloroplast. This organelle contains the most complex redox system in plants being composed of numerous players including thiol reductases, peroxidases, and glutathione-related enzymes. It seems likely that these proteins act together to adjust redox metabolism enabling plants to grow efficiently under both normal and stressed conditions. However, our knowledge concerning how these proteins interact and if they can compensate one another is relatively limited. This is in part due to the failure of considering these components from a systemic perspective. Here, we provide a systemic view of the chloroplastic-redox network highlighting how it operates and how its components co-operate to maintain efficient chloroplastic function. We further explore the cross-talk between chloroplastic-redox metabolism and that of other subcellular compartments. Given the complexity of plant redox metabolism and the compensatory role played by different redox systems, we argue that a unique possibility to understand this system is afforded by systems biology approaches and by characterizing mutants for multiple genes. Taking this into account, we highlight how gene co-expression and protein–protein network analyses coupled with different reverse genetic strategies could be used to reveal the function, potential redundancies, and complementarities among the components of the chloroplastic redox network.